KONSTRUKSI MAKNA PENDIDIKAN BAGI SISWA TUNARUNGU SEKOLAH MENENGAH ATAS (SLB) SRI MUJINAB KOTA PEKANBARU - Iza Guspa; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The meaning of education nowdays was a social constructed. This research have a purpose to acknowledge how is the meaning of education for students with disability (deaf). The informant of this research is the High School student in disability. The location of this research is in the Sri Munijab School for Disabilities, Pekanbaru city. This research using the purposive technique which determines the subject of research by terms and criteria. The researcher communicate with the deaf students with sign language, which the researcher have been learned before, and using the help of stationary and writing in the interview. Therefore, data was analyzed by a qualitative method. By this research, the researcher founds that the characteristic of disability or deaf students was very different. This can be depend on the factors of disability, family background, and their social life. Construction of the education meaning for disability students is education as a necessity for the future. But their standart of education in the future, it would be different for them, rather than the normal people, because of their disabilities and a different structure in social life. The necessity for the deaf or disability student is they can speak with the sign language and living their life in along with other normal people, and in future they can be employed or work independently without depending their life with others. The encouraging factors for the achievements of the disability students is a support from parents and teachers, and their spirit to get the science and knowledge. The Sri Munijab School of Disabilities in Pekanbaru have educated their students to be confident in their social life. The students not just educated to fulfill their needs, but also get prepared for their futureKeywords : Deaf, School of Disabilities